Antiulcer and Antioxidant Activity of a Lectin from Mucuna pruriens Seeds on Ethanol- induced Gastropathy: Involvement of Alpha-2 Adrenoceptors and Prostaglandins - Pinto, Isabela R.; Chaves, Hellíada V.; Vasconcelos, Auriana S.; de Sousa, Francisca Clea F; Santi-Gadelha, Tatiane; de Lacerda, José Thalles J. G.; Ribeiro, Kátia Alves; Freitas, Raul Sousa; Maciel, Lara Mendes; Filho, Samuel Mateus Pereira; Viana, Ana Flávia Seraine Custódio; de Almeida Gadelha, Carlos Alberto; et al. (Current Pharmaceutical Design, 2019)
Ethnopharmacological Relevance: Mucuna pruriens (Mp) belongs to Leguminosae family, it is native of tropical regions and used to treat several maladies such as urinary, neurological, and menstruation disorders, constipation, edema, fever, tuberculosis, ulcers, diabetes, arthritis, dysentery, and cardiovascular diseases. Mp seeds are rich in bioactive compounds, for instance, lectins, a heterogeneous group of proteins and glycoproteins with a potential role as therapeutic tools for several conditions, including gastric disorders. This study investigated the acute toxicity, gastroprotective, and antioxidant activities of a lectin from Mucuna pruriens seeds (MpLec) on ethanol-induced gastropathy model in mice. Material and Methods: Mice received MpLec (5 or 10 mg/kg; i.v.) and were observed for acute toxicity signs; in another experimental series, mice were pre-treated with MpLec (0.001; 0.01 or 0.1 mg/kg, i.v.), ranitidine (80 mg/kg, p.o.), or saline (0.3 mL/30g, i.v.) before ethanol 99.9% (0.2 mL/animal, p.o.), and euthanized 30 min after ethanol challenge. Macroscopic and microscopic gastric aspects, biochemical parameters (tissue hemoglobin levels, iron-induced lipid peroxidation, GSH content, SOD activity, and gastric mucosal PGE2) were measured. Additionally, pharmacological tools (yohimbine, indomethacin, naloxone, L-NAME) were opportunely used to clarify MpLec gastroprotective mechanisms of action. Results: No toxicity signs nor death were observed at acute toxicity tests. MpLec reduced ethanol-induced gastric damage, edema, and hemorrhagic patches formation, as well as decreased lipid peroxidation, SOD activity, and increased GSH content. Yohimbine and indomethacin prevented MpLec effects, suggesting the involvement of alpha-2 adrenoceptors and prostaglandins in the MpLec-mediated effects. Conclusion: MpLec does not present toxicity signs and shows gastroprotective and antioxidant activities via alpha-2 adrenoceptors and prostaglandins in the ethanol-induced gastropathy model.
Keywords: hemoglobin levels